KOMBINASI EKSTRAK DAUN BIDARADENGAN DAUN KEMANGI SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus DAN Escherichia coli. - Muhammad Richja As seffi; Yuli Wahyu Tri Mulyani; Annisa Mulia Anasis (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Infectious diseases are still at the top of the list of causes of illness and death in developing countries including Indonesia, Staphylococcus aureus and Escherichia coli are commonly found around the human environment, therefore prevention is needed to reduce infection by utilizing plants that have antibacterial effects such as bidara leaves with basil leaves. This study aims to determine the antibacterial activity of the combination of bidara leaf extract and basil leaves, and to determine the best combination concentration in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria compared to single extracts and positive controls. Using the diffusion method, the combination of dau bidara extract with basil leaves is K1 (0% + 100 %), K2 (20 + 80%), K3 (40% + 60%), K4 (50% + 50%), K5 (60 %+40%), K6 (80% + 20%), K7 (100% + 0%), K(-) Aquadest and K(+) Ampicillin. In the bacterial test (well diffusion method). The variable measured in this study was the diameter of the inhibition zone formed by the combination of extracts. Data analysis was tested using One Way Anova. The sig value for Staphylococcus aureus was 0.000≤0.05, while for Escherichia coli was 0.000≤0.05, it indicated that there was a significant difference between the test groups. The results of this study obtained the largest inhibition zone on bacteria, S. aureus, namely at K7 14.46 mm had a strong inhibitory response, while in bacteria E. Coli was found in K7 with the largest average value of 17.95 mm having a strong inhibitory response. This study can be concluded that the combination of bidara leaves and basil leaves has greater antibacterial power against Staphylococcus aureus and Escherichia coli bacteria than single extracts and positive control. Keywords: Ampicillin, antibacterial, Bidara leaves, basil leaves, diffuse